Fully‐Exposed Pd Cluster Catalyst: An Excellent Catalytic Antibacterial Nanomaterial. Issue 33 (24th July 2022) - Meng, Fanchi; Qin, Xuetao; Yang, Lini; Huang, Fei; Diao, Jiangyong; Cai, Xiangbin; Zhang, Di; Li, Ling; Zhu, Pengbo; Peng, Mi; Wang, Ning; Xiao, Dequan; et al.
Abstract: Exploring antibacterial nanomaterials with excellent catalytic antibacterial properties has always been a hot research topic. However, the construction of nanomaterials with robust antibacterial activity at the atomic level remains a great challenge. Here a fully‐exposed Pd cluster atomically‐dispersed on nanodiamond‐graphene (Pd n /ND@G) with excellent catalytic antibacterial properties is reported. The fully‐exposed Pd cluster nanozyme provides atomically‐dispersed Pd cluster sites that facilitate the activation of oxygen. Notably, the oxidase‐like catalytic performance of the fully‐exposed Pd cluster nanozyme is much higher than that of Pd single‐atom oxidase mimic, Pd nanoparticles oxidase mimic and even the previously reported palladium‐based oxidase mimics. Under the density functional theory (DFT) calculations, the Pd cluster sites can efficiently catalyze the decomposition of oxygen to generate reactive oxygen species, resulting in strong antibacterial properties. This research provides a valuable insight to the design of novel oxidase mimic and antibacterial nanomaterial. Abstract : The fully‐exposed Pd clusters are fabricated on defective nanodiamond‐graphene hybrid support (Pd n /ND@G) as an excellent oxidase mimic and antibacterial nanomaterial. The fully‐exposed Pd cluster nanozyme provides unique active adsorption sites, promoting the decomposition of O2 into reactive oxygen species (OH), which results in higher catalytic antibacterial properties than that of Pd single‐atom nanozyme and Pd nanoparticles nanozyme.